1988
DOI: 10.1111/j.1559-1816.1988.tb00014.x
|View full text |Cite
|
Sign up to set email alerts
|

I Can Resist Anything But Temptation: Adolescent Expectations for Smoking Cigarettes1

Abstract: Conformity to group pressure is widely considered a prime factor in experimentation with cigarettes. An alternative assumption is that the temptation to smoke arises out of the belief that cigarettes are instrumental in enhancing a sense of maturity, affiliation, and a reputation for autonomy. The present research assessed the relative saliency for both motive fulfillment and social pressure hypotheses in temptation dynamics and traced the causal influence of these factors on future expectations to smoke. Some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Narratives have long been seen as a source of therapeutic engagement (Polkinghorne, 1988). Although it was not the intention of this study to take a therapeutic approach to the narratives, it is evident that the process of telling their stories was meaningful to the adolescents we interviewed, in that it challenged them to articulate where they stood in relation to tobacco use and, in turn, to express their standpoint with respect to their own sense of self or agency (Covington & Omelich, 1988;Stein et al, 1998). The different ways that the youths spoke about tobacco revealed different possibilities for how their future will be shaped by tobacco.…”
Section: Discussionmentioning
confidence: 99%
“…Narratives have long been seen as a source of therapeutic engagement (Polkinghorne, 1988). Although it was not the intention of this study to take a therapeutic approach to the narratives, it is evident that the process of telling their stories was meaningful to the adolescents we interviewed, in that it challenged them to articulate where they stood in relation to tobacco use and, in turn, to express their standpoint with respect to their own sense of self or agency (Covington & Omelich, 1988;Stein et al, 1998). The different ways that the youths spoke about tobacco revealed different possibilities for how their future will be shaped by tobacco.…”
Section: Discussionmentioning
confidence: 99%
“…These challenges to dominant beliefs offer opportunities to a group which is searching for ways to express a growing sense of identity and independence from control and authority. In line with this, investigators have suggested that smoking provides a means for rejecting parental authority and for projecting an image of maturity and independence (Covington and Omelich, 1988;Leventhal and Cleary, 1980).…”
Section: The Significance Of Tobacco Branding To Under-age Smokingmentioning
confidence: 97%
“…smokers have also been reported (Cherry & Kiernan, 1976). More recently, there has been an interestibg accumulation of evidence suggesting that adolescents who smoke typically have lower self-esteem (Dielman, Campanelli, Shope, & Butchart, 1987;Piepe, Cattermole, Charlton, Morey, Morey, & Yerrell, 1988) and more prominent self-perceptions of personal incompetence and social unpopularity (Chassin, Presson, Sherman, Corty, & Olshavsky, 1981;Covington, & Omelich, 1988) than those who do not. In seeking to incorporate measures of personality into a multivariate psychosocial investigation of adolescent smoking, therefore, the attributes of N and self-esteem appear to be those most reliably and persuasively recommended by the available evidence.…”
mentioning
confidence: 99%